2017
DOI: 10.1001/jamaneurol.2017.2180
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Sleep-Disordered Breathing With Cognitive Function and Risk of Cognitive Impairment

Abstract: IMPORTANCE Growing evidence suggests an association between sleep-disordered breathing (SDB) and cognitive decline in elderly persons. However, results from population-based studies have been conflicting, possibly owing to different methods to assess SDB or cognitive domains, making it difficult to draw conclusions on this association. OBJECTIVE To provide a quantitative synthesis of population-based studies on the relationship between SDB and risk of cognitive impairment. DATA SOURCES PubMed, EMBASE, and Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
181
5
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 347 publications
(194 citation statements)
references
References 60 publications
2
181
5
6
Order By: Relevance
“…Sleep-disordered breathing has been associated with cognitive impairment across many domains including attention/working memory, global cognition, and delayed recall [12]. Similarly, the present study revealed significantly lower immediate recall scores in PCS patients with sleep apnea compared with those without, although it did not survive multiple comparisons.…”
Section: Sleep Apnea Pcs Symptoms and Neuropsychology Performancecontrasting
confidence: 45%
See 1 more Smart Citation
“…Sleep-disordered breathing has been associated with cognitive impairment across many domains including attention/working memory, global cognition, and delayed recall [12]. Similarly, the present study revealed significantly lower immediate recall scores in PCS patients with sleep apnea compared with those without, although it did not survive multiple comparisons.…”
Section: Sleep Apnea Pcs Symptoms and Neuropsychology Performancecontrasting
confidence: 45%
“…Sleep apnea is associated with a number of negative health and functional consequences [8,11]. This includes cognitive deficits [12], impaired neural repair via reduced synaptogenesis [8,13], and increased likelihood of motor vehicle or workplace accidents [8]. Some possible explanations for this increased incidence of obstructive sleep apnea (OSA) in patients with PCS may be medications used for symptomatic treatment of concussion like sedatives, hypnotics, and opioids as well as increased weight gain that commonly occurs after concussion [8].…”
Section: Introductionmentioning
confidence: 99%
“…This sleep disorder is related to a variety of health-related consequences across all age groups, including increased risk of cognitive impairment, depression, metabolic disorders, hypertension, cardiovascular disease, atrial fibrillation, and mortality. [43][44][45] Possibly, these outcomes might be in part explained by the association between OSA and SO.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances are common in the elderly, with as many as 50% of those aged over 65 years reporting a chronic sleep complaint (Neikrug & Ancoli-Israel, 2010). Numerous studies have examined the association between disturbed sleep and cognitive performance in the elderly (Leng, McEnvoy, Allen, & Yaffe, 2017;Shi et al, 2018). Some of these studies have reported that insomniatype symptoms in community-dwelling elderly people are associated with cognitive decline (Basta et al, 2018;Cricco, Simonisick, & Foley, 2001;Jelicic et al, 2002).…”
mentioning
confidence: 99%